Model Tata Kelola Data Terintegrasi Untuk Meningkatkan Daya Saing Bisnis Di Era Digital - Fathin Al Biyan Tanjung; Muhammad Irwan Padli Nasution (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
. In an increasingly competitive digital landscape, data has emerged as a strategic asset for organizations seeking to generate added value and achieve a sustainable competitive advantage. Despite its importance, many organizations struggle to manage data effectively due to fragmented systems and the absence of consistent governance standards. This study aims to develop an integrated data governance model designed to enhance operational efficiency and support data-driven decision-making. The methodology combines a comprehensive literature review, business needs analysis, and the design of a governance framework that integrates organizational, technological, and policy dimensions. The findings reveal that implementing an integrated data governance model significantly improves data quality, accelerates analytical processes, and fosters innovation within business operations. Consequently, this model offers a substantial contribution to strengthening business competitiveness in the digital era. Keywords: data governance, data integration, digital transformation, business competitiveness, information management